(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
This article elucidates the role of dietetics in addressing the symptoms of acid reflux, specifically focusing on Aamlapitta and GERD (Gastroesophageal Reflux Disease). Acid reflux poses a pervasive challenge, often causing discomfort and disrupting daily activities. However, through a comprehensive dietetic approach, individuals can effectively manage and alleviate these symptoms. This article synthesizes current research and practical insights to offer a holistic understanding of how dietary modifications can positively impact acid reflux. A common sickness of the gastrointestinal system, or Annavaha Srotasa, that affects people of all ages, genders, places, and climates may be Amlapitta, as described in several traditional Ayurvedic books. The 21st century is recognized as the modern period since it completely altered lifestyles and dietary patterns from earlier times. The majority of non-communicable diseases nowadays are caused by overindulgence in food items such as over-processed, under processed, and incompatible dietary preparations. Acharyas listed a number of dos and don’ts, including Ritucharya (a seasonal regime) and Dinacharya (a diurnal regime). The Ayurvedic teachings of Acharyas featured Pathya (healthy) and Apathaya (unhealthy) as a component in the treatment of ailments, in addition to being an essential part of the regimen of good health. In conclusion, this article underscores the pivotal role of dietetics in managing acid reflux and offers actionable insights to empower individuals in their journey toward symptom relief and improved quality of life.